Culinary Business Recommendation Application Using Promethee-II Method - Eko Budi Setiawan; Ferdika Bayu Herlambang; Angga Setiyadi (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This research discusses the application that can help determine consumer segmentation and provide recommendations for culinary business, including its selling price. The technology used in this research is a GPS sensor, Google API and JavaScript Object Notation. An Android-based mobile application platform uses GPS sensors to determine the new business location. This research used the Promethee-II method for the recommendation process, and it was based on certain criteria, particularly the factors influencing consumers to purchase. Five criteria were applied, and eight alternatives were calculated. The application was developed with the waterfall model. Based on the results of the alpha testing and user acceptance test, it is concluded that the application which was successfully built could provide prospective business makers with information regarding recommended types of culinary businesses including their selling price, recommended business location, and information about the consumer segmentation.